2008
DOI: 10.1073/pnas.0706211105
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent phosphorylation of Ser187 is required for SNAP-25-negative modulation of neuronal voltage-gated calcium channels

Abstract: Synaptosomal-associated protein of 25 kDa (SNAP-25) is a SNARE protein that regulates neurotransmission by the formation of a complex with syntaxin 1 and synaptobrevin/VAMP2. SNAP-25 also reduces neuronal calcium responses to stimuli, but neither the functional relevance nor the molecular mechanisms of this modulation have been clarified. In this study, we demonstrate that hippocampal slices from Snap25 ؉/؊ mice display a significantly larger facilitation and that higher calcium peaks are reached after depolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 62 publications
6
84
1
Order By: Relevance
“…Conversely, downregulation of SNAP-25, which increases evoked calcium transients [5], makes glutamatergic neurons more resistant to BoNT/A. These data suggest that susceptibility of neurons to BoNT/A results from the intrinsic calcium responsiveness to depolarization, which, among different factors, is modulated by the level of expression of SNAP-25 [5,6,28]. Interestingly, different intracellular calcium dynamics do not affect toxin penetration [11].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Conversely, downregulation of SNAP-25, which increases evoked calcium transients [5], makes glutamatergic neurons more resistant to BoNT/A. These data suggest that susceptibility of neurons to BoNT/A results from the intrinsic calcium responsiveness to depolarization, which, among different factors, is modulated by the level of expression of SNAP-25 [5,6,28]. Interestingly, different intracellular calcium dynamics do not affect toxin penetration [11].…”
Section: Discussionmentioning
confidence: 74%
“…In addition, the C-terminal region of SNAP-25 between BoNT/A and BoNT/E cleavage sites is also required for SNAP-25 modulation of voltage gated calcium currents [5,6].…”
Section: Reduction Of Neuronal Calcium Transients Enhances Sensitivitmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that voltagegated channel trafficking is regulated by neuronal activity (Kim et al, 2007). Pozzi et al (2008) demonstrated that the network activity can modulate neuronal voltage-gated calcium channels through the induction of protein phosphorylation. Interestingly, Servais et al (2007) observed that calcium entry into cerebellar Purkinje cells was reduced after early exposure to alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…This activation induces inhibition of presynaptic P/Q-type voltage-gated calcium channels, leading to reduction of glutamatergic synaptic transmission (32). Recently, it appears that this inhibition would involve the phosphorylation of SNAP-25 on Ser-187 by PKC (33,34). These results show the tight link between mGluR7 and scaffold/exocytosis proteins in the control of neurotransmission regulation via voltage-gated calcium channels.…”
Section: Tablementioning
confidence: 71%